2010
DOI: 10.1080/17421772.2010.493951
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Variances in UK Regional House Prices

Abstract: The returns of house price indices for the 13 UK regions are modelled using time series processes, including conditional variances. The first conclusion is that the UK follows the USA, with some regions displaying time-varying variances and others with constant variances. Secondly, there is limited evidence of an asymmetric component in six of the seven regions displaying autoregressive conditional heteroskedasticity. Thirdly, the results suggest that there are three distinct housing markets in the UK, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 22 publications
3
32
2
Order By: Relevance
“…The lag order of the estimated ARMA model for each property type is reported in Table . We have found that different ARMA model lag orders are present across the different property types, a finding which is in accordance with Miller and Peng () and Willcocks (), who highlight that housing markets are heterogeneous.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The lag order of the estimated ARMA model for each property type is reported in Table . We have found that different ARMA model lag orders are present across the different property types, a finding which is in accordance with Miller and Peng () and Willcocks (), who highlight that housing markets are heterogeneous.…”
Section: Resultscontrasting
confidence: 99%
“…where R it is the logarithmic house price change in month t for house property type i, and P it is the average monthly house price in month t for house property type i. It should be noted, however, that following Willcocks (2010), the returns are not smoothed or adjusted for inflation, as this could hide the impact of volatility changes over adjacent time periods. 1 In addition, in order to study the determinants of the Scottish housing market, we also include the Scottish unemployment rate, UK interest rate and UK CPI index in our dataset.…”
Section: Datamentioning
confidence: 99%
“…The significance of this analysis has implications for investment strategy in housing, especially for investors in multi-family real estate investment trusts (REITs) and single-family housing investment funds, as highlighted in . This paper also combines and extends two separate strands of research in housing: one stream on conditional analysis (e.g., Dolde & Tirtiroglu, 1997;Karoglou et al, 2013;Lin & Fuerst, 2014;Miles, 2008Miles, , 2011Morley & Thomas, 2011Willcocks, 2010;Zhou, 2016) and the other stream on unconditional analysis (e.g., . Fundamentally, I illustrate that the empirical analysis of the two schools of thought can be theoretically equivalent to a single-factor model.…”
Section: Introductionmentioning
confidence: 94%
“…Yet, despite its significance, little is known about how housing returns vary with price risk. While standard finance theory generally predicts a positive relationship between the market risk premium and conditional risk for risk-averse agents, a large body of empirical studies shows a negative relationship in housing markets (e.g., Dolde & Tirtiroglu, 1997;Karoglou, Morley, & Thomas, 2013;Lin & Fuerst, 2014;Miles, 2008Miles, , 2011Morley & Thomas, 2011Willcocks, 2010;Zhou, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation